Figura tatălui în proza lui Danilo Kiš - Tatjiana Petrika (ACROSS)
The present research focuses on elements of the father figure in Danilo Kiš's prose from a stylistic and semantic perspective. In the micro-novel, the figure of the father is a complex one, being at the centre of attention. Being the source of the 'family misfortune', Kiš demonstrates his own evolution. The father is inseparable from his three things glasses, black hat with brims and walking stick. Through these three things, Kiš is watching his son Andreas' game. The void created by his father's disappearance is a huge loss for the boy. Therefore, Eduard Sam is not only a missing father, but also a projection of the narrator's character, through which he describes various real-life situations.